The Effect of the COVID-19 Pandemic on Motivation in Teams: A Quantitative Analysis of Collective Efficacy and Team Cooperation. - Craft, Eleanor (2020)
The impact of the COVID-19 pandemic on employees and employers across the globe has been incredibly dramatic. It has changed the way organisations function, forcing many to partake in remote working and enforcing everyone to socially distance from one another, as per government guidelines. Within these unprecedented times it is vital that businesses can maintain their human capital to a high level in order to ensure they have a competitive advantage. This is why the motivation of employees is imperative to the smooth functioning of a business. Prior research has highlighted the importance of collective efficacy and cooperation within teams, which is the focus of this thesis.